COVID-19 and Acute Kidney Injury Outcomes in Hospitalized Patients Following SARS-CoV-2 Vaccination: A Case-Control Study - Froylan D. Martínez-Sánchez; Luis A. Bastida-Castro; José L. Torres-Cuevas; Julio A. Vasquez-Vasquez; Alejandra Diaz-Jarquin; Rafael Moreno-Novales; Joana Balderas-Juarez; Mauricio A. Salinas-Ramírez; Jose L. Hernández-Castillo; Erika K. Tenorio-Aguirre (Canadian Journal of Kidney Health and Disease)
Background: Acute kidney injury (AKI) is a frequent complication associated with severe COVID-19 and has been linked to increased mortality. While vaccination against SARS-CoV-2 has shown effectiveness in reducing severe COVID-19 outcomes, its impact on the development of AKI among hospitalized patients remains unclear. Objective: To evaluate the effect of SARS-CoV-2 vaccination on the incidence and severity of AKI and 28-day mortality among hospitalized patients with severe COVID-19. Design: Retrospective case-control study. Setting: Conducted at the Internal Medicine Department of Hospital General Dr. Manuel Gea González, Mexico, from April 2020 to December 2021. Patients: 413 patients over 18 with confirmed severe COVID-19 were included. Patients were categorized based on their vaccination status before COVID-19 infection. Measurements: Key outcomes included the incidence of AKI, progression to AKI stage 3, and 28-day mortality. AKI was defined according to the KDIGO criteria. Methods: Data were analyzed using univariate and logistic regression models to assess the association between vaccination status and the studied outcomes. Covariates included age, sex, BMI, type 2 diabetes, hypertension, and inflammatory markers. Results: Among the 413 patients, 70% developed AKI, with a median hospital stay of 10 days (range 6-17). Vaccinated patients had a significantly lower incidence of AKI compared with nonvaccinated patients (48.7% vs 74.9%; P < .001). After adjusting for confounding factors, vaccination was associated with lower odds of AKI (OR: 0.252, 95% CI: 0.140-0.452), AKI stage 3 (OR: 0.448, 95% CI: 0.205-0.981), and 28-day mortality (OR: 0.187, 95% CI: 0.064-0.544). Limitations: As a single-center retrospective study, generalizability is limited. In addition, vaccination data were obtained from medical records, and the completeness of vaccination could not be independently verified. Conclusions: SARS-CoV-2 vaccination was independently associated with a reduced risk of AKI, AKI stage 3, and 28-day mortality in hospitalized patients with severe COVID-19. These findings highlight the potential protective effects of vaccination against severe kidney complications in this population.